SAT0484 QUALITY OF LIFE IN JUVENILE IDIOPATHIC ARTHRITIS-ASSOCIATED UVEITIS: DO WE NEED A NEW ASSESSMENT QUESTIONNAIRE?. (June 2019) - Sestan, Mario; Grguric, Danica; Sedmak, Maja; Kifer, Nastasia; Frkovic, Marijan; Peric, Sanja; Potocki, Kristina; Vukojevic, Nenad; Jelusic, Marija
Abstract : Background: Uveitis, the most common extra-articular manifestation in juvenile idiopathic arthritis (JIA), occurs in 10-20% of patients. Although prognosis of uveitis within JIA (JIA-U) improved, complications still cause severe impairment of visual function in 25-33% of children that affects their psychophysical and psychosocial development and quality of life (QoL). Objectives: To study the QoL and it's dimensions in children suffering from JIA-U as well as to investigate is there any difference in childhood's and parent's perception of disease between the group of children with JIA-U and children with JIA without uveitis. Methods: The study included 42 children with JIA and their parents. Patients were divided into two groups. The first consisted of 21 children with JIA-U and the second of 21 children with JIA and no uveitis. Both groups of patients and their parents filled the Juvenile Arthritis Multidimensional Assessment Report questionnaire (JAMAR) for monitoring and assessing the health status of children with JIA. The variables used to test differences were: QoL, functional ability, pain level, disease activity estimation, and current emotional state of the child. The significance of differences between groups of children and parents was verified by the independent-samples t-test. The Pearson correlation coefficient was used for measurement of the strength of the linear relationship between variables. Results: There were no statistically significant differences in the JIA-U group and the control group in either of the examined variables. Although there is a tendency of higher scores in children with JIA-U, which indicates their worse functioning, higher pain intensity and worse current emotional state, these differences were not statistically significant. Two groups did not differ significantly in the assessment of their own overall functional ability, which was associated with experienced pain intensity. Stronger pain intensity was associated with dysfunction (r = 0.642, p <0.01) while a lower level of QoL was associated with more intense pain (r = 0.542, p <0.01) and poor current emotional state (r = 0.401, p <0.05). The activity of the disease in children was not significantly related to any determinant of the QoL. In contrast to children, parents of children with JIA-U estimated current emotional state of their children significantly worse (t = 2.05, p <0.05) and the overall level of functioning significantly lower than parents whose children did not have uveitis (t = 2.03, p <0.05). Conclusion: Since children with JIA evaluated the QoL equally well, whether they had uveitis or not, we can conclude that they are psychologically well adapted to their health status and cope well with different levels of pain. Unlike children with uveitis, their parents evaluated the current emotional state and overall functionality significantly worse compared to parents of children who did not have uveitis. These results support a need for the development of new uveitis specific questionnaires that will enable us better identification of patient's requirements. It is necessary to implement a holistic and multidisciplinary approach to assess the emotional functioning of the children and their families, and to devise appropriate psychosocial interventions for continuing support for ill children and their families. References: [1] Filocamo G, Consolaro A, Schiappapietra B, et al. A new approach to clinical care of juvenile idiopathic arthritis: the Juvenile Arthritis Multidimensional Assessment Report. J Rheumatol. 2011;38:938-53. Disclosure of Interests: None declared